Peran Kepuasan Kerja dalam Mengintervensi Pengaruh Kepemimpinan Transformasional dan Budaya Organisasi Terhadap Kinerja Karyawan - Isthofaina Astuty; Rahma Aditia (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The role of leadership is crucial in influencing the performance of organizational employees, as is the organizational culture. This influence becomes more significant when there is intervention in the perceived job satisfaction of employees. Therefore, this study aims to determine the role of transformational leadership and organizational culture on employee performance with job satisfaction as an intervening variable. The subjects of this study are the Center for Development and Empowerment of Cultural Arts Educators and Educational Personnel in Yogyakarta with permanent employees as research respondents. The sampling technique in this study is done using a census, and data collection methods involve distributing questionnaires directly to the respondents. Data analysis is conducted using Path Analysis with SPSS version 21, which consists of several stages of regression analysis. The Transformational Leadership questionnaire uses instruments from Bass and Avolio with 19 question items, the culture questionnaire uses 12 question items from Denison, the performance instrument uses a questionnaire from Viswesvaran, while job satisfaction uses a questionnaire developed by Gibson. The results of this study indicate that transformational leadership has a positive and significant influence on job satisfaction, organizational culture has a positive and significant influence on job satisfaction, transformational leadership has a positive and significant influence on employee performance, organizational culture has a positive and significant influence on employee performance, job satisfaction has a positive and significant influence on employee performance. The results also show that job satisfaction is able to mediate the influence of transformational leadership on employee performance, and job satisfaction is able to mediate the influence of organizational culture on employee performance. Based on these research findings, it is hoped that the Center for Development and Empowerment of Cultural Arts Educators and Educational Personnel in Yogyakarta will continue to prioritize the implementation of transformational leadership and maintain existing organizational culture, as well as uphold high levels of job satisfaction perceived by employees to maintain high employee performance.